2018
DOI: 10.1186/s12970-018-0245-8
|View full text |Cite
|
Sign up to set email alerts
|

Citrulline malate supplementation does not improve German Volume Training performance or reduce muscle soreness in moderately trained males and females

Abstract: BackgroundUse of supplements to aid performance is common practice amongst recreationally active individuals, including those without a sufficient evidence base. This investigation sought to assess whether acute supplementation with 8 g of citrulline malate (CM) (1.11: 1 ratio) would improve anaerobic performance.MethodsA randomised double blind placebo control trial was employed, using a counterbalanced design. We recruited recreationally active men and women to take part in an isokinetic chair protocol, base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(52 citation statements)
references
References 27 publications
1
50
0
1
Order By: Relevance
“…da Silva et al [48] also reported that acute citrulline malate supplementation (6 g) did not affect subjective soreness or serum CK compared to placebo during the 72 h following damaging (a main effect for time was observed for soreness and CK) leg press and hack squat exercise (3 × 8–12, 90% 10RM, 2 s eccentric contraction). Finally, a 2018 study [49] found that acute citrulline malate supplementation (~ 4.2 g citrulline) increased perceived soreness compared to placebo during the 72-h period after isokinetic knee extensions (10 × 10, 70%MVC) in resistance-trained males and females (Table 1).…”
Section: Main Textmentioning
confidence: 99%
“…da Silva et al [48] also reported that acute citrulline malate supplementation (6 g) did not affect subjective soreness or serum CK compared to placebo during the 72 h following damaging (a main effect for time was observed for soreness and CK) leg press and hack squat exercise (3 × 8–12, 90% 10RM, 2 s eccentric contraction). Finally, a 2018 study [49] found that acute citrulline malate supplementation (~ 4.2 g citrulline) increased perceived soreness compared to placebo during the 72-h period after isokinetic knee extensions (10 × 10, 70%MVC) in resistance-trained males and females (Table 1).…”
Section: Main Textmentioning
confidence: 99%
“…Bescós et al 4) reported that NO supplementation in untrained or moderately trained healthy participants showed positive effects on aerobic and anaerobic exercise tolerance, but not in highly trained participants. On the other hand, some studies concluded that single CM supplementation (6 or 8 g) prior to anaerobic, high-intensity, or resistance exercise, did not improve the performance or reduce fatigue in moderately or recreationally trained or untrained participants [23][24][25] . Cit supplementation of 3 g/day for 7 days in healthy and active, but not highly trained university level male collegiate track athletes, showed positive effects on exercise performance in the Wingate test in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that single CM supplementation of 8 g enhanced high-intensity anaerobic exercise performance [17][18][19] , and Cit supplementation of 2.4 or 6 g/day for 1 week enhanced aerobic cycling exercise performance 20,21) . On the other hand, single CM (6 -12 g) or Cit (6 g) supplementation showed no effect on exercise performance [22][23][24][25][26] . Thus, to date, only two studies have reported positive effects on exercise performance using a low dose (< 3 g) of Cit supplementation 20,27) .…”
Section: Introductionmentioning
confidence: 90%
“…Relatively recent studies have investigated the effects of both L-Arg and L-Cit supplementation on physiological responses and improving exercise performance [9,10,26,27,35,44,[46][47][48]. Exercise intensity (i.e., velocity or power output) refers to the amount of work that can be accomplished to perform a given activity, often expressed as a percentage of an individual's VO 2max , or maximal power output, both typically measured using incremental exercise testing [49].…”
Section: L-arg and L-cit On Physiological Response And Exercise Perfomentioning
confidence: 99%